Pepsin as a Marker of Reflux Aspiration in Children With Esophageal Atresia: A Pilot Study - Upendran, Yadhavan; Leach, Steven T.; Singh, Harveen; McBride, James; Thomas, Paul S.; Belessis, Yvonne; Krishnan, Usha (Frontiers in Pediatrics, 2020)
Abstract Background: Reflux aspiration secondary to gastroesophageal reflux disease (GERD) is one of the causes of chronic gastrointestinal and respiratory morbidity in children with esophageal atresia (EA). Currently there are no simple, validated non-invasive tests for the diagnosis of reflux aspiration in children. Objectives The aim of this pilot study was to investigate pepsin detected in exhaled breath condensate (EBC) and saliva as a potential non-invasive marker of reflux aspiration in children with EA. Methods: EBC and saliva samples were prospectively collected from children with EA aged between 5 and 18 years attending a multidisciplinary EA Clinic. Pepsin in the samples was assayed by two methods, a commercial lateral flow device, the Peptest™ and an enzyme-linked immunosorbent assay (ELISA) and correlated with validated gastrointestinal and respiratory symptom questionnaires and objective measures of GERD and respiratory function. Results: EBC were collected from 18 children with EA, 15/18 also provided salivary samples. Pepsin was not detected in any of the EBC samples using the Peptest™ and only 1/14 (7.1%) samples by the ELISA. However, pepsin was detected in 33% and 83% of saliva samples when analyzed with Peptest™ and the ELISA respectively. Salivary pepsin levels were significantly higher in children with reflux symptoms or wheeze. Pepsin was detected by the Peptest™ in the saliva of 5/5 (100%) children with histological evidence of reflux esophagitis compared with 0/2 (0%) in children with normal histology (p = 0.048). Conclusions: Salivary pepsin was detected in a large proportion of children with EA and was significantly associated with GERD symptoms or wheeze. The role of salivary pepsin as a potential non-invasive marker of reflux aspiration in children with EA needs further validation in future studies with larger cohorts.